PENGARUH LINGKUNGAN TEMPAT TINGGAL DAN SIKAP SISWA TEHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X IPA SMA SUNGGUMINASA GOWA - Abdul Hadi; Rizky Ramadhana; Andi Tenriawaru (Jurnal Penalaran dan Riset Matematika, 2023)
This study aims to determine the effect of the living environment and students' attitudes towards mathematics learning outcomes of SMA Sungguminasa Gowa students. The type of research "Ex-Post Facto" is correlational with a sample of 30 students from class X IPA 2 SMA Sungguminasa Gowa who were selected using simple random sampling. The problem being investigated is the effect of the environment where students live and attitudes towards mathematics learning outcomes of SMA Sungguminasa Gowa students. Data collection techniques using instruments: (1) Questionnaire of the environment where students live and attitudes, (2) Mathematics learning outcomes test. The results of the descriptive statistical analysis show (1) The average score of the mathematics learning outcomes of class X IPA 2 SMA Sungguminasa Gowa for the academic year 2022/2023 is 82.800 from an ideal score of 100 with a standard deviation of 12.505. (2) The average score of the neighborhood is 46.767 out of an ideal score of 65 with a standard deviation of 7.601. (3) The average score of student attitudes is 50.933 from the ideal score of 70 with a standard deviation of 8.718. The results of inferential statistical analysis show (1) the living environment has a positive and significant effect on the mathematics learning outcomes of class X IPA 2 SMA Sungguminasa Gowa with tcount=2.201>ttable=2.052. (2) Student attitudes have a positive and significant effect on mathematics learning outcomes (Y) of class X IPA 2 SMA Sungguminasa Gowa with tcount=3.208> ttable=2.052. (3) The living environment and students' attitudes together have a positive and significant effect on the mathematics learning outcomes of class X IPA 2 SMA Sungguminasa Gowa with Fcount=63.710>Ftable=3.340 with an R2 contribution of 82.5%.